CHAT APPLICATION IN LOCAL AREA NETWORKS NETWORK (LAN) ORIENTED INTERNET BY USING THE MICROSOFT VISUAL BASIC 6.0 - Yus Dwi Harumaningsih; Elly Agustina J, SKom, MMSI (Jurnal Sistem Informasi, 2004)
With the growing advances in computer technology, the more developed also othertechnologies that support forward technology, such that telecommunicationstechnology. With the combina tion of both technological progress above, then apartfrom the existence of local networks (LAN), there is a global network for the entireworld kind an internet network that is very fortunate in telecommunications channelsin use.Internet is one medium that has many uses and benefits, among which, the Internetcan be used as a means of chatting. Chatting in the beginning is a tool that utilizes theinternet network is useful as a medium of communication and exchange ofinformation. However, in its development, chatting for most people is only useful as ameans of entertainment only. Furthermore, the chat is only developed for the Internetnetwork and can not be done in a local network using the communication media islocal (LAN).Given the above problems, the authors use the Winsock authors utilize existingfacilities in Microsoft Visual Basic 6.0, which is used as an interface betweencomputers in a network that each computer can communicate with each other. Meansof a special chat to apply in the local computer network (LAN) connected or not intothe internet network is a software application that is used instead of the xisting chatsoftware.